Smart calling, 3rd edition eliminate the fear, failure, and rejection from cold calling - Sobczak, Art (Gildan Audio, 2020)
In the newest edition of Smart Calling: Eliminate the Fear, Failure, and Rejection from Cold Calling, celebrated author and sales trainer Art Sobczak packs even more powerful insight into what many people fear: prospecting by phone for new business. This bestselling guide to "never experiencing rejection again" has consistently found its way into the Top 20 in Amazon's Sales category, because its actionable sales tips and techniques have helped many minimize their fears and eliminate rejection.The newest edition builds upon the very successful formula of the last edition to help sales professionals take control of their strategy and get more yeses from their prospects. With new information, this info-packed release provides powerful sales insights, including: the foundational concepts of cold calling, featuring real-life examples you can carry with you into your sales career; multiple case studies and messaging from successful salespeople across the globe, providing even more insight into what works and what's a waste of your time; and new methodologies that are proven to push you past your fear and into the world of successful prospecting.If you're failing to convert your prospects into dollars, Smart Calling will help you push past the obstacles holding you back until you're an expert at taking a "no" and turning it into a "yes."